New Real Environment Simulation Models on Railway Network - Karel Sotek; Hynek Bachraty; Jan Ruzbarsky; Viliam Tavac (Communications - Scientific letters of the University of Zilina, 2003)
Transport network simulation models become inseparable part of the innovation processes in transport technology. They approach current operation especially in conjunction with the realization of the information and control systems. References about partial applications were published in various occasions. The authors try to offer integrated up-to-date information about result of their work concerning described area. This name is used for the models whose parameters and data structures encompass terms and parameters adapted from the real system in a considerable amount.